Pupils Participation in a Technology-Rich Environment: A Study of Pupil Perspective on Learners’ and Teachers’ Roles - Öberg, Johanna; Nouri, Jalal (International Journal of Emerging Technologies in Learning (iJET), 2021)
It has been argued that participation as involvement as well as taking part in decision making is a fundamental part of learning. The first large arena for experiencing this for many young people is the school. This paper investigates how 16 pupils at grade eight view their own and their teacher’s role when it comes to facilitating participation. The pupils are interviewed the semester after a long researcher led participation project and the interviews are analyzed using thematic analysis. The analysis identifies four different types of participation from the pupils’ responses. These four types can be connected to passive and active participation as well as participation as involvement and participation as influence.